Psychological impacts of the SARS-CoV-2 Pandemic on the World Population: An Integrative Review (Research, Society and Development, 2021)
SARS-CoV-2, the cause of the current covid-19 pandemic, presents itself as a problem for public health, in which, in addition to concerns about physical health, it also brings concerns about psychological suffering. The objective of this study was to analyze the scientific evidence about the psychological impacts and other alterations in the mental health of the Brazilian population in the SARS-CoV-2 Pandemic, identifying the main factors that lead the world population to unleash mental health problems and present strategies for preventing and coping with the psychological impacts suffered by the world population in the pandemic. This study is an integrative review, in which the sample of 27 articles was composed from a survey of data through a search in the Virtual Health Library (VHL) where the electronic databases used in the research are indexed: SCIELO (Scientific Eletronic Library Online), LILACS (Latin American and Caribbean Literature on Health Sciences), BDENF (Nursing Database), PubMed (NCBI) and Google Academic, in the years 2020 to 2021. The descriptors were crossed with each other using the Boolean AND marker. The collection was carried out from August to November 2020. The importance of implementing strategies and/or interventions so that the population has access to emotional support measures in the face of the SARS-CoV-2 pandemic, whether in person or online. Taking into consideration the different populations affected, it is recommended to address the mental health consequences of the pandemic and psychological interventions in response to individual needs during the course of the pandemic outbreak.